2018
DOI: 10.1038/s41429-018-0066-7
|View full text |Cite
|
Sign up to set email alerts
|

Bafilomycin C1 induces G0/G1 cell-cycle arrest and mitochondrial-mediated apoptosis in human hepatocellular cancer SMMC7721 cells

Abstract: Bafilomycin C1, which was isolated from Streptomyces albolongus in our previous work, exhibited strong cytotoxicity against several cancer cell lines. This study aimed to evaluate its antitumor effect on human hepatocellular cancer SMMC7721 cells and the underlying mechanism in vitro and in vivo. MTT assay revealed that bafilomycin C1 retarded SMMC7721 cell growth and proliferation. Western blot and real-time qPCR analysis revealed that bafilomycin C1 caused partial G0/G1 phase cell-cycle arrest, downregulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…The above results confirmed that BN-3b stimulated ROS accumulation in C. albicans. The excessive ROS production can lead to mitochondrial dysfunction, mainly characterized by the loss of MMP and decrease of ATP generation 28 . Our current study showed that the MMP levels of C. albicans cells were significantly reduced in a dose-dependent manner after treated with BN-3b.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The above results confirmed that BN-3b stimulated ROS accumulation in C. albicans. The excessive ROS production can lead to mitochondrial dysfunction, mainly characterized by the loss of MMP and decrease of ATP generation 28 . Our current study showed that the MMP levels of C. albicans cells were significantly reduced in a dose-dependent manner after treated with BN-3b.…”
Section: Discussionmentioning
confidence: 99%
“…BN-3b, AMB (Sigma-Aldrich) and FLC (Solarbio Science & Technology Co., Ltd., Beijing, China) were dissolved in dimethyl sulphoxide (DMSO) to prepare 150.0 mg/mL, 10.0 mg/mL and 10.0 mg/mL of stock solutions and stored at −20 °C. Working solutions of BN-3b, AMB, and FLC were prepared by diluting the stock solution with DMSO prior to use 28 . N-acetylcysteine (Beyotime Biotechnology Co., Shanghai, China) was dissolved in phosphate-buffered saline (PBS) to prepare 0.5 M of stock solution and stored at −20 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, by increasing p21 and p53 levels, mRNA and protein expression is notably reduced. Hepatocellular carcinoma cells are induced by bafilomycin C1 partial cell‐cycle arrest and activated apoptotic pathway both in vitro and in vivo , together with decreasing mRNA and protein levels of CDK2, increasing p21 and p53 …”
Section: Biology and Regulation Of Cdks In Hccmentioning
confidence: 99%
“…Hepatocellular carcinoma cells are induced by bafilomycin C1 partial cell- cycle arrest and activated apoptotic pathway both in vitro and in vivo, together with decreasing mRNA and protein levels of CDK2, increasing p21 and p53. 57 UCN-01 is also known as 7-hydroxystaurosporine and functions as a kinase inhibitor. UCN-01 inhibits checkpoint kinase 1 (CHK1), CHK2, protein kinase A, and protein kinase C, in addition to CDK2.…”
Section: Cyclin-dependent Kinasementioning
confidence: 99%